Albian high-resolution biostratigraphy and isotope stratigraphy: The Coppa della Nuvola pelagic succession of the Gargano Promontory (Southern Italy) - LUCIANI V.; JENKYNS H. C.; COBIANCHI, MIRIAM (2004)
High-resolution δ13C and δ180 curves, calibrated against planktonic foraminiferal and calcareous nannofossil biostratigraphy, are provided for the upper Aptian–lower Cenomanian pelagic succession of the Gargano Promontory (Coppa della Nuvola section, southern Italy). The succession consists of two superimposed formations: the Marne a Fucoidi and the Scaglia (lower portion only). According to our integrated biostratigraphy, the entire succession spans the latest Aptian (planktonic foraminiferal T. bejaouaensis and calcareous nannofossil R. angustus Zones) and early Cenomanian stages (R. cushmani Zone CC9c). The Marne a Fucoidi–Scaglia transition falls in the late Albian (R. ticinensis Zone; CC9a+b Subzones). The high-resolution δ13C curve from the Coppa della Nuvola section can be subdivided into characteristic segments. Four negative shifts of δ13C are recorded, followed by increasing values in, respectively, the early Albian (C11, C12), the early late Abian (C14, C 15), the late Albian (C16, C17), and the early Cenomanian (C22). The late Albian carbon-isotope event, corresponding to the Oceanic Anoxic Event (OAE) 1d or Breistroffer Event, is possibly missing in the Coppa della Nuvola section as a result of condensation or erosion (C19–C20?). Even if, in the section studied, carbon-rich levels are not recorded (though some stratigraphic intervals are covered by Quaternary deposits in the lower portion), it is likely that the lower Albian (T. primula; P. columnata Zones) and the upper Albian (T. praeticinensis Subzone– R. subticinensis Zone; R. achlyostaurion Zone) positive δ13C peaks succeeding negative trends in δ13C (C11–C12; C16–17) record the pattern of global carbon burial, documented in other areas of the Gargano Promontory and elsewhere and connected to the OAE1b and OAE1c. Some or all of the negative δ13C shifts may record the introduction of isotopically light carbon into the ocean−atmosphere system from the dissociation of gas hydrates. The δ18O curve of the Coppa della Nuvola section shows a similar ...